MATURITY AND SPAWNING OF THE SPOTTED HERRING, HERKLOTSICHTHYS PUNCTATUS (RUPPELL) FROM THE ANDAMAN SEA - Marichamy, R (Indian Journal of Fisheries, 2011)
Herklotsichthys punciatus has been found to attain sexual maturity at an average size of 125 mm total length in the Andaman waters. Observations on the seasonal progression of ova indicated the sharp biannual spawning habit of the fish. The percentage occurrence of mature fish, fluctuations of the relative ovary weight during different months and ova diameter frequency indicated that spawning occurs first in May-June and again in October-November. Fecundity has been found to vary from 6,530 to 10,690 in specimens ranging 115-144 mm total length.